Clinical features and electroclinical evolution in 22 cases with epileptic spasms without hypsarrhythmia. Issue 1 (13th March 2020) - Koichihara, Reiko; Hamano, Shin‐ichiro; Daida, Atsuro; Nonoyama, Hazuki; Ikemoto, Satoru; Hirata, Yuko; Matsuura, Ryuki
ABSTRACT: Aim : This study aimed to investigate the general presentation of epileptic spasms without hypsarrhythmia (ESwoH) and retrospectively determine whether there are differences in treatment effects related to ACTH therapy, long‐term seizure outcome, and evolution of EEG features according to pre‐treatment EEG patterns. Methods : According to the pattern of background activity, we divided our cohort into two groups: Group 1: normal background activity or with localized intermittent slow waves; Group 2: intermittent slow waves appearing generalized or in two or more lobes. Subjects included 22 children (Group 1: n =10; Group 2: n =12) diagnosed with ESwoH who received treatment from 2007 to 2017. Results : The median age at onset of epileptic spasms was 5.5 months and the follow‐up period lasted for 40.5 months. ACTH therapy was performed for seven patients from Group 1 and eight patients from Group 2. Only one patient from Group 2 responded to ACTH. Patients receiving effective treatments at early stages had excellent seizure outcome. Refractory cases included six patients in Group 1 and eight patients in Group 2; subsequent follow‐up EEGs indicated hypsarrhythmia in one patient in Group 1 (17%) and six patients (75%) in Group 2, including one patient whose EEG pattern indicated progression to Lennox‐Gastaut syndrome. Conclusions : Overall, ACTH is ineffective for patients with epileptic spasms without hypsarrhythmia. The EEG may indicate possible future development of hypsarrhythmia if epileptic spasms are resistant to treatment, especially in patients with diffuse slow waves on pre‐treatment EEG. The efficacy of treatment introduced at early stages from onset may predict long‐term seizure outcome.